A time for the humanities : futurity and the limits of autonomy - Bono, James J. (James Joseph); Dean, Tim, 1964-; Ziarek, Ewa Płonowska, 1961- (Book collections on Project MUSE., 2008)
Bringing together contributors from disciplines including philosophy, political theory, intellectual theory and literary studies, this volume addresses the conceptual foundations of the humanities and the question of their future.